Receptor-mediated activation of ceramidase activity initiates the pleiotropic actions of adiponectin - Holland, William L; Miller, Russell A; Wang, Zhao V; Sun, Kai; Barth, Brian M; Bui, Hai H; Davis, Kathryn E; Bikman, Benjamin T; Halberg, Nils; Rutkowski, Joseph M; Wade, Mark R; Tenorio, Vincent M; et al. (Nature medicine, 2011)
The protein hormone adiponectin is known to have many beneficial systemic effects, including promoting cell survival, anti-inflammation and insulin sensitivity. Phil Scherer and his colleagues have found that these pleiotropic effects are mediated by a ceramidase activity associated with the two known isoforms of the adiponectin receptor. The adipocyte-derived secretory factor adiponectin promotes insulin sensitivity, decreases inflammation and promotes cell survival. No unifying mechanism has yet explained how adiponectin can exert such a variety of beneficial systemic effects. Here, we show that adiponectin potently stimulates a ceramidase activity associated with its two receptors, AdipoR1 and AdipoR2, and enhances ceramide catabolism and formation of its antiapoptotic metabolite—sphingosine-1-phosphate (S1P)—independently of AMP-dependent kinase (AMPK). Using models of inducible apoptosis in pancreatic beta cells and cardiomyocytes, we show that transgenic overproduction of adiponectin decreases caspase-8-mediated death, whereas genetic ablation of adiponectin enhances apoptosis in vivo through a sphingolipid-mediated pathway. Ceramidase activity is impaired in cells lacking both adiponectin receptor isoforms, leading to elevated ceramide levels and enhanced susceptibility to palmitate-induced cell death. Combined, our observations suggest a unifying mechanism of action for the beneficial systemic effects exerted by adiponectin, with sphingolipid metabolism as its core upstream signaling component.